Apoptosis Pada Sperma Sebagai Petanda Adanya Gangguan Kesuburan Pria - Syamsul Hadi, Restu (Majalah Kesehatan Pharmamedika, 2011)
Semen analysis includes assessment of volume, color, viscosity, pH, concentration, motility, and morphology as standard procedures to semen analysis. It has known that correlation between apoptosis and spermatogenesis. Apoptosis is a mechanism regulating spermatogenesis in humans, and there are clear differences in molecular markers of apoptosis between males with normal sperm parameters and those with abnormal sperm parameters. Sperm apoptotic apoptosis has been shown to increase after testicular injury, such as exposure to toxics, varicocle, testicular torsion, hormonal deprivation and genetic abnormalities. It has been found that the number of sperm with Fas expression was low in subjects with normal sperm parameters but high in men with abnormal sperm parameters. It has been reported that the number sperm with Fas expression was low in subjects with normal sperm parameters but high in men with abnormal sperm parameters. Male infertility appears to be positively correlated with increased levels of apoptotic sperm. Sperm DNA damage and sperm apoptosis have been considered as useful marker of male fertility disorder.